2022
DOI: 10.5021/ad.2022.34.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Development of In Vitro Co-Culture Model to Mimic the Cell to Cell Communication in Response to Urban PM2.5

Abstract: Background Airborne particulate matter (PM), a widespread air contaminant, is a complex mixture of solids and aerosols composed of particles suspended in the air. PM is associated with inflammatory responses and may worsen inflammatory skin diseases. However, the mechanisms through which PM affects atopic dermatitis (AD) remain unclear. Objective To establish an in vitro model that more accurately mimics AD using human keratinocyte (HaCaT), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…These findings suggest that PM 2.5 exposure is a risk factor for lung cancer progression and that the AhR-TMPRSS2-IL18 pathway is a potential target for the development of new therapies against this disease ( Wang et al, 2023 ). Moreover, in an innovative in vitro model that simulates cell interactions occurring in skin during atopic dermatitis, it was shown that PM 2.5 exposure led to an upregulation of proinflammatory cytokines, including IL-1α, IL-1β, IL-6, IL-4, IL-13, and TNF-α in a co-culture assay ( Roh et al, 2022 ).…”
Section: General Characteristics Of Particulate Matter Subtypesmentioning
confidence: 99%
“…These findings suggest that PM 2.5 exposure is a risk factor for lung cancer progression and that the AhR-TMPRSS2-IL18 pathway is a potential target for the development of new therapies against this disease ( Wang et al, 2023 ). Moreover, in an innovative in vitro model that simulates cell interactions occurring in skin during atopic dermatitis, it was shown that PM 2.5 exposure led to an upregulation of proinflammatory cytokines, including IL-1α, IL-1β, IL-6, IL-4, IL-13, and TNF-α in a co-culture assay ( Roh et al, 2022 ).…”
Section: General Characteristics Of Particulate Matter Subtypesmentioning
confidence: 99%
“…The triple-cell culture was pretreated with Poly I:C (10 μg/mL) and IL-1α (10 ng/mL) to induce an AD-like phenotype. After 24 hours, the cell cultures were treated with ASC-exosomes and PM at a concentration of 25 μg/cm 2 , according to previous studies [7,8,12]. The plates were incubated at 37˚C for an additional 24 hours.…”
Section: Reagent and Exosome Treatment Of The Cellsmentioning
confidence: 99%
“…An AD-like triple-cell model with three different cell types, including HaCaT, HDF, and HMC-1 cells, was used to investigate the cell-to-cell interactions associated with AD [12]. We compared the intracellular uptake of PKH67-labeled ASC-exosomes in HaCaT cells (Fig 1A Therefore, the treatment time of the exosomes was selected as 24 and 48 hours.…”
Section: The Cellular Uptake Levels Of Asc-exosomes In An Ad-like Tri...mentioning
confidence: 99%
See 2 more Smart Citations